Routine Intraoperative Hepatic Sonography Does Not Affect Staging or Postsurgical Hepatic Recurrence in Pancreatic Adenocarcinoma. (1st January 2014) - Mui, Leonora W.; Pursell, Lisa J.; Botwinick, Isadora C.; Allendorf, John D.; Chabot, John A.; Newhouse, Jeffrey H.
Abstract : Objectives: The purpose of this study was to evaluate the utility of intraoperative sonography of the liver in the staging of pancreatic adenocarcinoma and its impact on the rate of postoperative tumor recurrence in the liver. Methods: We performed a retrospective analysis of the rate in which intraoperative sonography of the liver changed surgical management in 470 surgical candidates with pancreatic adenocarcinoma. In postsurgical patients, we performed a χ 2 analysis to examine whether the patients who underwent hepatic intraoperative sonography had a lower rate of recurrent disease in the liver within the first 6 months of surgery compared to patients who did not undergo the procedure. Conclusions: Hepatic intraoperative sonography affected management in less than 1% of cases, detecting 1 unsuspected liver metastasis in 470 surgical patients with pancreatic adenocarcinoma. Of 3 patients with equivocal liver lesions identified on preoperative computed tomography or magnetic resonance imaging, hepatic intraoperative sonography excluded metastasis and cleared all the patients for surgical resection. There was no significant difference in postoperative liver recurrence between the group of patients who received intraoperative sonography before resection and patients who did not have the procedure done ( P > .99). Conclusions: Routine intraoperative sonography of the liver does not affect staging of pancreatic adenocarcinoma. It may be useful for evaluating equivocal lesions.